Malaysia Ministry of Education's selection of poems for the form four and form five new literature component - Chew, Fong Peng; Tan, Li Chin (2011)
The introduction of English as a second language has been eleven years down the road in Malaysia. This study attempts to investigate the level of acceptability or suitability of the new set of poems for the Form Four and Form Five literature component in order to know the effectiveness of these selected poems. Pertinent issues like factors that affect students' comprehension and suitable activities to aid the learning of the poems are also being highlighted in this paper. The findings of this study are contributed by 360 of Form Four students who are currently studying the new selected poems. The overall findings show that the Ministry of Education's selection of poems in suitable for the new Form Four and Form Five literature component and although students face a few difficulties in comprehending the poems, there are suitable activities in the classroom as a solution to these problems.